Kinetika Reaksi Demineralisasi Isolasi Kitin Dari Cangkang Ebi - Subkhan Maulana; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitin is a naturally abundant polymer and most of it was used as a surfactan and cosmetic raw material. Chitin be able to derive from natural source like shrimp shell waste. The aims of this research were to study the effect of various of time reaction and HCl concentration towards both of calcium concentration reduction and demineralization kinetic model with approach to shrinking core model (SCM). There are 3 stage of model which be able to use: Film layer diffusion, Diffusion through the outcome layer and Chemical reaction. It was began with deproteination at first with NaOH 3,5 % and continued with demineralization using HCl at concentration 0,3 N; 0,6 N; 0,9 N and 1,2 N with variation of reaction time at 15, 30 and 15 minute. The specimen had dried in the oven before the calcium analyzed. The results showed calcium concentration decrease along with increasing of HCl concentration. It get kinetic model at concentration 0,3 N of HCl usage with form: 1−(